Darmvorbereitung bei elektiven kolorektalen Resektionen in Deutschland 2017 - Buia, Alexander; Post, Stefan; Buhr, Heinz J.; Hanisch, Erik; Hanisch, Ernst (Der Chirurg, 2019)
BackgroundThe morbidity after colorectal resection is still high. Perioperative i.v. antibiotic administration has become established as the standard to decrease the wound infection rate. An ongoing discussion is the status of preoperative mechanical bowel preparation. There seems to be evidence that mechanical bowel preparation in combination with administration of oral non-resorbable antibiotics significantly decreases the rate of anastomotic leakage and postoperative wound infections.ObjectiveIn order to obtain an overview on the state of preoperative preparation before elective colorectal surgery in Germany, a survey was initiated among the members of the German Society of General and Visceral Surgery.Material and methodsIn March 2017 the 5200 members of the German Society of General and Visceral Surgery (DGAV) received via email a link to an online survey on bowel preparation before elective colorectal surgery.ResultsA total of 557 colleagues answered the questionnaire online. Mechanical bowel preparation with orthograde lavage was the predominant method for bowel preparation prior to colon resection in over 50%. In rectal surgery with primary anastomosis and planned protective stoma, mechanical bowel preparation with orthograde lavage dominated with 76.5%. An oral antibiotic administration alone and in combination with mechanical bowel preparation for colon resection was used by less than 10% and 2%, respectively and ca. 11 % for rectal surgery both with and without mechanical bowel preparation.ConclusionIn contrast to the evidence in the current literature to carry out preoperative mechanical preparation of the bowel in combination with an oral antibiotic administration prior to colorectal resection, in practice these recommendations have not become established among the participants of this survey.
Gesehen am 14.10.2019